Evaluation of student motivation to further their study in MSc.IT program using intrinsic and extrinsic motivation / Siti Aisyah Ibrahim - Ibrahim, Siti Aisyah (2016)
Motivation can affect both new learning and the performance of previously learned skills, strategies, and behaviors. Motivation is an internal state or condition that arouses us to action, directs and persists our behavior and engages us in certain activities. In this paper the concepts of motivation, including extrinsic motivation and intrinsic motivation will be explored. It describes how motivation becomes a major concern in human behavior and is defined as a desire that urges us to do something. Master Science Information Technology (MSc.IT) is one of the programs that offered for part time student in UiTM. There are many students who take the MSc.IT program in Faculty of Computer and Mathematical Sciences (FSKM) in part time mode which virtually all students are individuals who have worked in government and the private sector. The study explores motives and factors for MSc.IT students to further their study especially in part time mode. The aim of this paper is to evaluate the student motivation to further their study in Msc.IT Program using Extrinsic and Intrinsic Theory. The objectives of this research is to analyze student's motivation based on Extrinsic and Intrinsic Theory and to identify the factors that motivates the students to do their MSc. IT in UiTM. This project uses quantitative method for data collection and the normality, reliability, frequency and correlation between the data has been tested using Statistical Package for the Social Sciences (SPSS). For the extrinsic motivation, there are four factors has been discussed which is promotion, salary, and benefit package. Meanwhile, for intrinsic motivation, there are six factors has been discussed which is social contact, independence, power, challenge, curiosity and social status. In the result, what can be summarized is the students might have both intrinsic and extrinsic elements of motivation which is depends on their demo graphic factors.